2014
DOI: 10.4103/0970-0218.137150
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of vitiligo in a rural set up of Gujarat

Abstract: Introduction:Vitiligo is an acquired depigmentary condition caused by inactivation or destruction of melanocytes in epidermis and hair follicle. Worldwide incidence of 1% has been reported; similar to various dermatological clinics in India. Widespread prejudice, ignorance, taboos, lack of scientific appraisal, and confusion of vitiligo with leprosy makes it an immense psychological stress.Aim:To know the clinical profile of vitiligo patient with associated cofactors.Materials and Methods:Total 1,010 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 11 publications
14
27
0
Order By: Relevance
“…17 Children younger than 20 years represent 35.5% of patients in a Nigerian cohort 18 and age of onset before 20 years of age was noted in 47.8% of patients in a Gujarati cohort. 19 Mean age of onset can be as low as 6.9 years in Indian children 12 years and younger 17 and as high as 17.4 years in an unselected Saudi Arabian mixed pediatric and adult population. 20 Family history appears to be associated with earlier age of onset.…”
Section: Epidemiology Of Pediatric Vitiligomentioning
confidence: 99%
See 1 more Smart Citation
“…17 Children younger than 20 years represent 35.5% of patients in a Nigerian cohort 18 and age of onset before 20 years of age was noted in 47.8% of patients in a Gujarati cohort. 19 Mean age of onset can be as low as 6.9 years in Indian children 12 years and younger 17 and as high as 17.4 years in an unselected Saudi Arabian mixed pediatric and adult population. 20 Family history appears to be associated with earlier age of onset.…”
Section: Epidemiology Of Pediatric Vitiligomentioning
confidence: 99%
“…21 The prevalence of vitiligo by gender is usually close to if not equal, with some studies supporting female predilection in the youngest age groups. Vora et al 19 described a Gujarati cohort of 1100 patients of all ages in which 57.3% were female individuals and 42.7% were male individuals. In a cohort of 268 Indian children 12 years and younger, 56.7% were girls (n = 152) and 43.3% were boys (n = 116).…”
Section: Epidemiology Of Pediatric Vitiligomentioning
confidence: 99%
“…Vitiligo is an acquired idiopathic disease that appears as skin depigmented patches (Vora, Patel, Chaudhary, Mehta, & Pilani, ). Its prevalence varies from 1% to 4% in different parts of the world and affects all races (Khaitan, Kathuria, & Ramam, ); moreover, it is more common among people with autoimmune diseases and children whose parents are suffering from this disease.…”
Section: Introductionmentioning
confidence: 99%
“…It could be concluded that the simultaneous use of NB-UVB and topical piperine has a remarkable effect on treatment of vitiligo. KEYWORDS herbal, pigmentation, piperine, topical treatment, UVB, vitiligo 1 | INTRODUCTION Vitiligo is an acquired idiopathic disease that appears as skin depigmented patches (Vora, Patel, Chaudhary, Mehta, & Pilani, 2014). Its prevalence varies from 1% to 4% in different parts of the world and affects all races (Khaitan, Kathuria, & Ramam, 2012); moreover, it is more common among people with autoimmune diseases and children whose parents are suffering from this disease.…”
mentioning
confidence: 99%
“…The prevalence of vitiligo exceeds 8% in certain regions of the world [reviewed in [1]]. Although the lesions are asymptomatic, vitiligo negatively impacts the quality of patients' lives [2,3].…”
Section: Introductionmentioning
confidence: 99%